2018
DOI: 10.1089/jpm.2018.0102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Comfort and Confidence of Neonatal Clinicians in Providing Palliative Care

Abstract: Research reveals the importance of neonatal palliative education and suggests further development of interdisciplinary neonatal palliative care teams to improve clinicians' professional confidence and personal comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…This research provides insight into the conflicts and cultural challenges surrounding neonatal end-of-life care and further highlights the urgent needs of neonatal clinicians for interdisciplinary, culturespecific palliative care education and communication skills training in order to promote confidence and decrease moral distress experienced while providing end-of-life care to infants in the NICU. 21,22 This is the first research comparing the knowledge and attitudes among neonatal clinicians toward neonatal palliative care in mainland China. However, the study was cross-sectional and conducted in one province in China, so results may differ in other areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research provides insight into the conflicts and cultural challenges surrounding neonatal end-of-life care and further highlights the urgent needs of neonatal clinicians for interdisciplinary, culturespecific palliative care education and communication skills training in order to promote confidence and decrease moral distress experienced while providing end-of-life care to infants in the NICU. 21,22 This is the first research comparing the knowledge and attitudes among neonatal clinicians toward neonatal palliative care in mainland China. However, the study was cross-sectional and conducted in one province in China, so results may differ in other areas.…”
Section: Discussionmentioning
confidence: 99%
“…This research provides insight into the conflicts and cultural challenges surrounding neonatal end-of-life care and further highlights the urgent needs of neonatal clinicians for interdisciplinary, culture-specific palliative care education and communication skills training in order to promote confidence and decrease moral distress experienced while providing end-of-life care to infants in the NICU. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…These items were in three of the eight domains including the structure and process of care, physical aspects of care, and care of the imminently dying and reflect areas of PNPC that physicians often have more experience with. These findings were not surprising since previous work has suggested that physicians are often more confident than nurses in the practice of perinatal and neonatal palliative care (18,19). After participation in the training course, these differences disappeared.…”
Section: Discussionmentioning
confidence: 52%
“…The results of another study in Iran suggested that the performance of the nurses working in NICUs is affected by their age ( 35 ). The results of a study in Taiwan suggested that providing PC for neonates hospitalized in NICUs by clinical specialists is affected by age and relevant training ( 36 ). A study in China showed that nurses who had the experience of participating in courses on death-related issues had a more positive attitude toward caring for terminally ill patients ( 25 ).…”
Section: Discussionmentioning
confidence: 99%